Women's financial literacy, inclusion, digital finance, and cultural value: an ethnography study in West Kalimantan - Ary, William Wendy (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
Gender equality is a concerning issue and women have been fighting for it for many years including Indonesian women. Existing literatures had shown that fintech empirically related to financial literacy, financial inclusion, and digital finance adoption but very little attention given to women’s cultural background especially from ASEAN perspective and very little studies examined this topic from gender perspective. Ethnography methodology was used to explore the perspective of Chinese, Dayak, and Malay (CDM) women living in West Kalimantan about their financial literacy, financial inclusion, digital finance adoption, and cultural value. This study found that CDM women have quite good level of financial literacy in average. Then, this study also found some interesting results regarding CDM women’s financial inclusion. Moreover, it was also found that CDM women have had been using e-wallet in daily activities and there were four reasons behind it namely promotion, bill payment, minimising paper money usage, and daily purchasing. New financial technologies help CDM women in daily economic activities. Moreover, CDM women trusted current digital financial services and technologies in general. Finally, only Chinese participants said that their cultural and ethnicity background affect their perspective towards money management.